Dynamic photoluminescence studies of vertical n+ n-GaAs Al0.2Ga0.8As structures designed for microwave electronics - erškus, A; Kundrotas, J; Nargelien, V; Su ied lis, A; Ašmontas, S; Gradauskas, J; Johannessen, A; Johannessen, E (Physica scripta, 2013)
Vertical structures of n+ n-GaAs Al0.2Ga0.8As designed as radiation detectors for microwave electronics have been the subject of continuous wave and dynamic photoluminescence studies. Both light emission lifetimes and photoluminescence spectra were investigated to find the possible mechanisms of carrier recombination. The characteristic time of free exciton emission in the n-GaAs layer corresponds to 0.73 ns at a temperature of 3.6 K, 1.1 ns at 77 K and 1.3 ns at 300 K. The band-to-band transition lifetimes in the n-GaAs layer are found to be 2.8 ns at 77 K and 3.8 ns at 300 K. The recombination lifetime of a free electron via an acceptor was measured to be 22 ns in the GaAs layer and 16 and 32 ns in the n-Al0.2Ga0.8As layer, reflecting the two different transitions observed. The short characteristic time of the excitonic transitions in the n-Al0.2Ga0.8As layer permits the excitonic emission to follow laser excitation pulses down to the order of 200 ps.